Cercarial Dermatitis at Public Bathing Sites (Region Zealand, Denmark): A Case Series and Literature Review - Azmi Al-Jubury; Anette Bygum; Eva SusannaTracz; Charlotte Näslund Koch; Kurt Buchmann (Karger Publishers, 2021)
During recent years, we have observed an increasing occurrence of cercarial dermatitis in Denmark. We here describe 5 new cases from 2019 to 2020 associated with bathing in lakes Esrum sø, Furesø, and Ringen with emphasis on clinical symptoms and their relation to previous exposure to bird schistosome cercariae. In 2020, 2 patients from Furesø suffered from different severity of clinical symptoms after morning bathing in the same lake. We suggest that the differential symptoms may be explained by primary versus secondary exposure to the immunogenic pathogen.